Rekonstruksi Pemahaman Berkat Berdasarkan Tafsiran Kejadian 12:1-3 Di Gereja Toraja Jemaat Kollo Klasis Tondon - Patandianan, Mordica (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
Blessing is the most important part of life of christians, expecially in Gereja Toraja Jemaat Kollo Klasis Tondon.  Many people assume that Lord’s blessing is just a good things, while the distress, suffering, and other disaster is not a blessing of the Lord. This comprehension also developing in church members of Jemaat Kollo Klasis Tondon. This is inspiring the writer to do research, how theology of Lord’s blessing in Genesis 12:1-3 and how the comprehension that should be owned by church members of Jemaat Kollo Klasis Tondon about Lord’s blessing. The purpose of this study is to know the theology of Lord’s blessing according to the Holy Bible in Genesis 12:1-3 and the comprehension that should be owned by church members based on exegesis Genesis 12:1-3. Writer use historical analysis and background analysis as well as text analysis , and expalin how comprehension of the church member about Lord’s blessing and how the comprehension that should be owned by church members based on exegesis Genesis 12:1-3 with using a qualitative research and study fieldwork.